Aggressive priming online: Facebook adverts can prime aggressive cognitions. (July 2015) - Buchanan, Tom
Highlights: Unattended stimuli in our environments can prime thoughts, feelings and behaviour. Violence-related website adverts primed aggressive cognition. Mood and person perception were not affected by exposure to violent adverts. Individuals differed in the extent to which they were primed. There is scope for genuine internet adverts to prime aggressive cognition. Abstract: Through the process of priming, incidental stimuli in our environments can influence our thoughts, feelings and behaviour. This may be true of incidental stimuli in online environments, such as adverts on websites. Two experiments ( N = 325, N = 331) showed that the mere presence of advertisements with violent content on a simulated Facebook page induced higher levels of aggression-related cognition in comparison to non-violent adverts ( d = 0.56, d = 0.71). In a subsequent word recognition task, participants primed with the violent stimuli 'remembered' more actually-unseen violence-related words than did the control participants. That is, they reported recognising violent words they had not actually seen. However, priming with violent adverts had no effect on mood or person perception. A third correlational study ( N = 131) examined whether variance in the extent of priming could be attributed to individual differences in aggressiveness. Participants' aggressiveness was unrelated to their scores on the aggressive cognition measure. These studies established that website adverts with violent content could prime aggressive cognitions. Individuals differed in the extent to which they experienced the priming effect, and this was not attributable to their levels of trait aggressiveness. No effects of priming were found on either mood state or person perception.